2013
DOI: 10.1051/0004-6361/201220013
|View full text |Cite
|
Sign up to set email alerts
|

Magellan/MMIRS near-infrared multi-object spectroscopy of nebular emission from star-forming galaxies at 2 <z< 3

Abstract: Aims. To investigate the ingredients, which allow star-forming galaxies to present Lyα line in emission, we studied the kinematics and gas phase metallicity of the interstellar medium. Methods. We used multi-object near-infrared spectroscopy with Magellan/MMIRS to study nebular emission from z 2−3 starforming galaxies discovered in three MUSYC fields. Results. We detected emission lines from four active galactic nuclei and 13 high-redshift star-forming galaxies, including Hα lines down to a flux of (4 ± 1)E-17… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 76 publications
(179 reference statements)
1
36
0
Order By: Relevance
“…The ∆v Lyα,r value has been measured in more than 60 LAEs (McLinden et al 2011;Finkelstein et al 2011;Hashimoto et al 2013;Guaita et al 2013;Chonis et al 2013;Shibuya et al 2014b;Song et al 2014;Erb et al 2014). These studies have shown that LAEs at z ∼ 2 − 3 have a mean ∆v Lyα,r of ≃ 200 km s −1 , which is significantly smaller than that of LBGs at a similar redshift, ∆v Lyα,r ≃ 400 km s −1 (e.g., Steidel et al 2010;Rakic et al 2011;Kulas et al 2012).…”
Section: Lyα Main Red Peak Velocity Offsets ∆Vlyαrmentioning
confidence: 99%
“…The ∆v Lyα,r value has been measured in more than 60 LAEs (McLinden et al 2011;Finkelstein et al 2011;Hashimoto et al 2013;Guaita et al 2013;Chonis et al 2013;Shibuya et al 2014b;Song et al 2014;Erb et al 2014). These studies have shown that LAEs at z ∼ 2 − 3 have a mean ∆v Lyα,r of ≃ 200 km s −1 , which is significantly smaller than that of LBGs at a similar redshift, ∆v Lyα,r ≃ 400 km s −1 (e.g., Steidel et al 2010;Rakic et al 2011;Kulas et al 2012).…”
Section: Lyα Main Red Peak Velocity Offsets ∆Vlyαrmentioning
confidence: 99%
“…To estimate z sys , we started with the VUDS redshift as a guess, and we fit together the CIII]1908 emission line and the continuum around it. We used the optimize.leastsq python function (as applied also in Guaita et al 2013) by assuming a Gaussian profile, that the continuum has a well-defined slope (linear fit), and including the VUDS noise spectrum in the minimization procedure. This noise contains the information of the observation and the instrumental uncertainty.…”
Section: Systemic Redshiftmentioning
confidence: 99%
“…An alternative selection criterion based on other strong emission lines would have the drawback that we could only select a smaller number of galaxies over a smaller redshift range, e.g., Hα emitters can be selected at z < ∼ 0.5. Finally, the choice of a sample of strong [O iii] emitters has also been motivated by the aim of collecting a representative and statistically significant sample of star-forming galaxies that would be easily detectable at higher redshifts (z ∼ 2−3) in deep wide-field NIR surveys (e.g., van der Wel et al 2011;Atek et al 2011;Xia et al 2012;Guaita et al 2013;Maseda et al 2013Maseda et al , 2014. Since they would be affected by similar biases, our sample is intended to offer a valuable benchmark for future direct comparison with other probes of strong emission-line galaxies at higher redshifts.…”
Section: The Eelg Sample Selectionmentioning
confidence: 99%